A Theory of International Boycotts - Abdoulaye Ndiaye (CESifo GmbH, 2024)
Calls to boycott a foreign country aim to push a share of domestic consumers to cut their consumption of goods imported from the targeted country. How do boycotts differ from sanctions? Should boycotters target all of the country's products, or should they focus on a restricted set of sectors? I answer these questions in a canonical Ricardian model. The model allows me to determine the optimal targeted boycott strategies and trace out the Pareto frontier of the domestic boycotters' and foreign country's welfare.
Keywords: 330; Boykott; Sanktion; Konsumentenboykott; Außenwirtschaftstheorie; Neoklassische Theorie; Pareto-Optimum